Association of common genetic variation in the protein C pathway genes with clinical outcomes in acute respiratory distress syndrome. Issue 1 (December 2016) - Sapru, Anil; Liu, Kathleen; Wiemels, Joseph; Hansen, Helen; Pawlikowska, Ludmilla; Poon, Annie; Jorgenson, Eric; Witte, John; Calfee, Carolyn; Ware, Lorraine; Matthay, Michael
Abstract Background Altered plasma levels of protein C, thrombomodulin, and the endothelial protein C receptor are associated with poor clinical outcomes in patients with acute respiratory distress syndrome (ARDS). We hypothesized that common variants in these genes would be associated with mortality as well as ventilator-free and organ failure-free days in patients with ARDS. Methods We genotyped linkage disequilibrium-based tag single-nucleotide polymorphisms in the ProteinC, Thrombomodulin and Endothelial Protein C Reptor Genes among 320 self-identified white patients of European ancestry from the ARDS Network Fluid and Catheter Treatment Trial. We then tested their association with mortality as well as ventilator-free and organ-failure free days. Results The GG genotype of rs1042580 (p  = 0.02) and CC genotype of rs3716123 (p  = 0.002), both in the thrombomodulin gene, and GC/CC genotypes of rs9574 (p  = 0.04) in the endothelial protein C receptor gene were independently associated with increased mortality. An additive effect on mortality (p  < 0.001), ventilator-free days (p  = 0.01), and organ failure-free days was observed with combinations of these high-risk genotypes. This association was independent of age, severity of illness, presence or absence of sepsis, and treatment allocation. Conclusions Genetic variants in thrombomodulin and endothelial protein C receptor genes are additively associated with mortality in ARDS. These findings suggest that genetic differences may be at least partially responsible for the observed associations between dysregulated coagulation and poor outcomes in ARDS.